Dielectric relaxations and dielectric response in multiferroic BiFeO3 ceramics - Hunpratub S. (2014)
Single-phase multiferroic BiFeO3 ceramics were fabricated using pure precipitation-prepared BiFeO3 powder. Dielectric response of BiFeO3 ceramics was investigated over a wide range of temperature and frequency. Our results reveal that the BiFeO3 ceramic sintered at 700 °C exhibited high dielectric permittivity, and three dielectric relaxations were observed. A Debye-type dielectric relaxation at low temperatures (-50 to 20 °C) is attributed to the carrier hopping process between Fe2+ and Fe3+. The other two dielectric relaxations at the temperature ranges 30-130 °C and 140-200 °C could be due to the grain boundary effect and the defect ordering and/or the conductivity, respectively. © 2009 American Institute of Physics.